Profitabilitas, Likuiditas, Leverage, dan Ukuran Perusahaan: Sebuah Analisis Islamic Social Reporting (Isr) Pada Perusahaan yang Terdaftar di Jii - Hendri Affandi; Meta Nursita (Majalah Ilmiah Bijak, 2019)
This study aimed to examine the impact of Profitability, Liquidity, Leverage, and CompanySize towards the expression of Islamic Social Reporting (ISR) by the corporateslisted and registered under the Jakarta Islamic Index (JII) within 2012-2016. This study employed Purposive Sampling method with a total of 25 companies taken as the sample in the present study. Data analysis process followed the following steps; descriptive statistical test, multicollinearity test, model fit test, regression model feasibility test, and hypothesis test. Statistical method used is panel data regression analysis. The result showed that profitability had partially significant impact on ISR; liquidity strongly had significant impact on ISR; leverage and company size had no significant impact on ISR. In addition, simultaneously, the results showed that the four aspects examined had statistically significant impact on ISR.This study aimed to examine the impact of Profitability, Liquidity, Leverage, and CompanySize towards the expression of Islamic Social Reporting (ISR) by the corporateslisted and registered under the Jakarta Islamic Index (JII) within 2012-2016. This study employed Purposive Sampling method with a total of 25 companies taken as the sample in the present study. Data analysis process followed the following steps; descriptive statistical test, multicollinearity test, model fit test, regression model feasibility test, and hypothesis test. Statistical method used is panel data regression analysis. The result showed that profitability had partially significant impact on ISR; liquidity strongly had significant impact on ISR; leverage and company size had no significant impact on ISR. In addition, simultaneously, the results showed that the four aspects examined had statistically significant impact on ISR.